Proliferação, angiogênese, apoptose e expressão da cicloxigenase-2 no ovário de ratas com disfunções tireoidianas e na placenta e ovário de ratas com hipotireoidismo - Juneo Freitas Silva (2011)
Two different experiments were performed. In experiment 1, the effect of hypo-and hyperthyroidism on the proliferative activity, apoptotic, angiogenic and COX-2 expression in the ovary of non-pregnant rats was evaluated. In experiment 2, placental and fetal development and luteal activity in hypothyroid rats was evaluated. In experiment 1, 60 adult female Wistar rats were distributed equally in groups hypothyroid, hyperthyroid and euthyroid (control) in the stages of proestrus-estrus and metestrus-diestrus. The immunohistochemical expression ofCDC-47, VEGF, Flk-1 and COX2 and apoptosis by TUNEL assay in ovarian follicles and corpora lutea were evaluated. In experiment 2, 36 adult female Wistar rats were distributed equally in control and hypothyroid groups. The number and weight of fetuses and the rate offetal death was determined, as well as the morphometric characteristics, the immunohistochemical expression of CDC-47 and VEGF and the number of apoptotic cells in the placental disk. In the ovaries of pregnant rats were evaluated the number of corpora lutea, the expression of CDC-47, COX-2, VEGF and Flk-1 and apoptosis by TUNEL assay. Thehypo-and hyperthyroidism were induced by daily oral administration of propylthiouracil (1 mg / animal) and L-thyroxine (50 mg / animal), respectively. In experiment 1, thyroid dysfunction were induced for three months and in the second experiment, the drug began five days beforemating and ended at 19 days gestation. The animals were sacrificed at 14 and 19 days of gestation. The data were submitted to ANOVA and means were compared by Student's t or SNK. In experiment 1, it is concluded that thyroid dysfunctions differentially affect the levels ofproliferative activity, angiogenesis and apoptosis and the expression of COX-2 in the ovaries of female rats, and these effects are dependent of the phase of the estrous cycle. We conclude in experiment 2 that hypothyroidism affects placental and fetal development by altering theproliferative activity, apoptotic, and angiogenic placental disc and also alters ovarian lutealactivity.